DINAMIKA DAYA SAING EKSPOR UDANG BEKU DAN OLAHAN INDONESIA DI PASAR INTERNASIONAL - Samsul Mashari; Rita Nurmalina; Suharno Suharno (Jurnal Agribisnis Indonesia, 2019)
During the past eleven years, shrimp is the leading commodity of Indonesian fishery exports, especially the types of frozen and preserved shrimp that have a considerable export value. However, Indonesian exports value growth of both shrimp products are lower than its competitors. The purpose of this study is to analyze the level of competitiveness and the exports dynamics position of frozen and preserved shrimp in Indonesia among competing countries in the international market. The method used is Revealed Comparative Advantage (RCA) and Dynamic Revealed Comparative Advantage (DRCA). The method is used to analyze changes in the competition level for 11 years (2007-2017), which is divided into 2 periods namely 2007-2012 and 2012-2017. The results showed that both frozen shrimp and preserved shrimp had a competitiveness in the international market. The competitiveness of Indonesian preserved shrimp tends to increase among 9 main competitors in two periods. In the first period, the competitiveness of Indonesian preserved shrimp was in the falling star position while in the second period reached the best position, namely rising star. On the other hand, the competitiveness of Indonesian frozen shrimp position in the first period was in the lost opportunity and reached the rising star position in the second period. Indonesia needs to increase exports of frozen and preserved shrimp products by ensuring the availability of raw materials and improving quality in exporting frozen shrimp and preserved shrimp.